“Que obra fez Deus!”: o lifecasting entre a vigilância e o espetáculo na sociedade conectada 24/7 - Ferreira, Diego Lima (2015)
This research aims to study the lifecasting, especially one in which the lifecaster transmits your life uninterrupted, as an phenomenon of 24/7 conected society, such as Jonathan Crary (2014) understands and as technical mediation, intensified by the expansion of internet access, by increasing the connection speed, the cheapening of the cost of equipment, the use of mobile devices and a lot of surveillance practices that has been developing, particularly from the early 1980s. Undertaken a literature review, a web archival research (survey videos, testimonials and stories published about the pioneers in 24/7 lifecasting and his followers and the organization of a personal archive made up of recordings of broadcasts and prints chats) and questionnaires application to lifecasters and lifeviewers, we tried to draw a historical route and to identify the motivations that led them to this practice. The case study systematically accompanied the transmission of the three most important lifecasters of today (among those using the Portuguese, English and Spanish): the American Frank Taylor, the Danish Jan Billy and the Finn Ari Aarne Antero Kivikangas (Cyberman). The lifecasting was analyzed on the basis of four main axes: as a member of the 24/7 society, as a form of surveillance, spectacle of self and resistance. The reasons presented by lifecasters and lifeviewers are in line with current practices in the 24/7 connected society in which surveillance systems, exposure of personal life and the consumption habits have in lifecasting an extreme exemple.